(3MGTjI Ydi GdMGTjI GdNaQjI Ydi GdTQM GdLOjO ddJLQjOs - (3GdcjdGfj ` GdLjdGfj, eMeO GdcjdGfj, GdeYQha Hehdi eTSG, J (B1098(3g` (B1687(3es ((3OGQ GdSdWfIs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg Pj GdeLO hGdHgGA (B... (3gPg JYdjbGJ GJabJ efj (B... (3Ydi eHMK EdgjGJ GdJLQjO hTQMg GdLOjO hGdMGTjI GdJj YdbgG GdYdGeI GdNaQj YdjgG (B... (3GYde Cf ehVhY GdYdes
(3BNQgG (B:s
(3BNQgG(B: (3hSGFQ GdChUGa, Cj HTQW Sdj SGFQ GdChUGa jYfj djS dg (B.. (3UaI ceGdjI RGFOI Ydi PGJg hgPG ZTGQI Ydi faj GdcKQI HYO GdPGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 609s
(3GdPQjYI, L (B6: 49s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds